2017
DOI: 10.1016/j.jhep.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Trunk mutational events present minimal intra- and inter-tumoral heterogeneity in hepatocellular carcinoma

Abstract: Trunk alterations arise at early stages of cancer and are shared among all malignant cells of the tumor. In order to identify trunk alterations in HCC, we characterized early stages of hepatocarcinogenesis represented by dysplastic nodules and small lesions. Mutations in TERT, TP53 and CTNNB1 genes were the most frequent. Analyses in more advanced lesions showed that mutations in these same genes were shared between different regions of the same tumor and between primary and metastatic tumors, suggesting their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
119
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(133 citation statements)
references
References 35 publications
10
119
1
3
Order By: Relevance
“…We confirmed a clonal distribution of known drivers, such as TERT promoter, CTNNB1, and TP53 ( Supplementary Fig. 3c, Supplementary Table 2), with only one tumor region (H4.a) depicting a subclonal mutation of CTNNB1 19 . Using DNA Sanger sequencing, we validated 11 expressed mutations predicted as damaging (Supplementary Table 3).…”
Section: Resultssupporting
confidence: 70%
“…We confirmed a clonal distribution of known drivers, such as TERT promoter, CTNNB1, and TP53 ( Supplementary Fig. 3c, Supplementary Table 2), with only one tumor region (H4.a) depicting a subclonal mutation of CTNNB1 19 . Using DNA Sanger sequencing, we validated 11 expressed mutations predicted as damaging (Supplementary Table 3).…”
Section: Resultssupporting
confidence: 70%
“…required in the early step of carcinogenesis in cirrhosis and TERT promoter mutations are the only recurrent mutations in the driver genes observed in both low-grade and high-grade dysplastic nodules (between 5 to 20% of mutations) and up to 60% of early HCCs. 52,53 These results indicate that TERT is a gatekeeper gene which is mutated very early in liver carcinogenesis, reactivating telomerase in order to bypass senescence of hepatocytes in cirrhosis. Moreover, transcriptomic analysis of premalignant nodules in cirrhosis and early HCCs have highlighted that activation of MYC, early in the course, could be involved in the process of malignant transformation 54 whereas activation of other signalling pathways such as transforming growth factor-b (TGFb), WNT or NOTCH occurred later during hepatocarcinogenesis.…”
Section: Mechanisms Of Malignant Transformation On Cirrhosismentioning
confidence: 93%
“…89,90 Preliminary data in HCC have suggested that the main driver genes such as CTNNB1, TP53 and TERT are clonal trunk mutations and are consequently ideal therapeutic targets. 53,[90][91][92] However, more data are required to clarify this using ultradeep sequencing in combination with methylation and transcriptomic analysis, in order to capture the complexity of intratumor heterogeneity in large cohorts of HCC. Another type of genomic heterogeneity observed in HCC is inter-tumour heterogeneity that can be related to de novo independent carcinogenesis on a background of cirrhosis and/or intrahepatic metastasis (Fig.…”
Section: Key Pointsmentioning
confidence: 99%
“…4 In this regard, the impact of intratumor heterogeneity in single-biopsy predictions is still debated despite recent studies showing that driver gene mutations are common between different regions of the tumour. 77,78 Traditionally, new therapies were compared with standard of care or placebo to demonstrate greater efficacy of the new drug. Despite this being the recommended trial design in HCC, 4,33 some studies after SHARP used non-inferiority designs to challenge sorafenib in first-line.…”
Section: Positive Phase III Clinical Trialsmentioning
confidence: 99%